Field trials on the repellent activity of four plant products against mainly Mansonia population in western Ethiopia - Hadis, Mamuye; Lulu, Mesﬁn; Mekonnen, Yared; Asfaw, Teffera (Phytotherapy research, 2003)
The repellent activity of essential oils of lemon eucalyptus (Eucalyptus maculata citrodion), rue (Ruta chalepensis), oleoresin of pyrethrum (Chrysanthemum cinerariaefolium) and neem (Azadiracta indica) have been ﬁeld tested as 40%, 50% and 75% solutions in coconut oil against populations of mosquitoes consisting mainly of Mansonia in Gambella, western Ethiopia. A latin square design was used to randomize the test subjects for possible individual differences for mosquito attraction. Repellency was evaluated as the percentage protection. Deet was included in the study for comparison. All the plant products manifested repellency. At 50% concentration at which the highest repellency was recorded the protection was 91.6%, 87.0%, 96.0%, 97.9% for rue, neem, pyrethrum and deet, respectively. The essential oil of lemon eucalyptus was not tried at this concentration. At a 40% concentration deet, lemon eucalyptus and pyrethrum were signiﬁcantly (p < 0.05) more effective than rue and neem. At a 50% concentration, deet and pyrethrum were signiﬁcantly better (p < 0.05) than rue and neem. At a 75% concentration concentration, deet and lemon eucalypus performed signiﬁcantly better (p < 0.05) than pyrethrum and neem. The difference between pyrethrum and neem was also signiﬁcant (p < 0.01). Copyright © 2003 John Wiley & Sons, Ltd.